Just wars and moral victories : surprise, deception and the normative framework of European war in the later Middle Ages - Whetham, David (History of warfare, 2009)
By exploring the moral and legal context of medieval strategic thinking, this work explains how the use of surprise and deception could, in certain circumstances, be reconciled with the practise of chivalric warfare.